2020
DOI: 10.1186/s10020-020-00154-6
|View full text |Cite
|
Sign up to set email alerts
|

Conditional deletion of HDAC4 from collagen type 2α1-expressing cells increases angiogenesis in vivo

Abstract: Background: HDAC4 is a key regulator of chondrocyte hypertrophy and skeletal development, but it is not clear whether the increase in vascular invasion at growth plates is related to HDAC4 expression. To determine it, we investigated the relationship between HDAC4 and angiogenesis in both in vivo and in vitro models. Methods: HDAC4 was deleted in Col2α1-Cre; HDAC4 fl/fl mice. Growth of the Col2α1-Cre; HDAC4 d/d mice was compared with HDAC4 fl/fl mice at postnatal days 2, 4, 6, and 8. X-rays were taken to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Our data regarding both chondrocytes and the synovial membrane are in line with those reporting an increased expression of CD31 and CD34 in the knee joints of the Col2α1-Cre; mice by postnatal days 14 and 21 [ 55 ]. As both CD31 and CD34 are markers of a number of progenitor cells, their expression in the OA might be an indication of an attempt of the cells to proliferate and differentiate as well as a kind of endochondral bone formation [ 55 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our data regarding both chondrocytes and the synovial membrane are in line with those reporting an increased expression of CD31 and CD34 in the knee joints of the Col2α1-Cre; mice by postnatal days 14 and 21 [ 55 ]. As both CD31 and CD34 are markers of a number of progenitor cells, their expression in the OA might be an indication of an attempt of the cells to proliferate and differentiate as well as a kind of endochondral bone formation [ 55 ].…”
Section: Discussionsupporting
confidence: 90%
“…Gao et al proposed that the stronger the compatibility of online education platform, the more reasonable the layout design of online education platform, the clearer the video images, and the better the audio quality, the more the college students who are willing to continue to use English online education platform for learning [11]. Kong proposed that the online education platform promoted by institution of higher learning will make full use of high-tech elements such as cloud technology and big data artificial intelligence to innovate online education mode and reshape learners' behavior.…”
Section: Research Status Of Online English Learningmentioning
confidence: 99%
“…Previous studies have shown that decreased expression of HDAC4 activates the RUNX2 promoter, leading to upregulation of VEGF expression, thus promoting vascular formation on the growth plate. [ 48 ] To investigate the relationship between miR‐29a/HDAC4/RUNX2 and VEGF expression, we examined the gene and protein expression of VEGF in different groups in vitro. Immunofluorescence staining (Figure 8C) showed a significant decrease in HDAC4 expression and a significant increase in RUNX2 and VEGF expression in the HMP@Agomir‐29a‐Exo group.…”
Section: Resultsmentioning
confidence: 99%